Reasons nursing students choose the nursing profession and their nursing image perceptions: A survey study - Esengül Elibol; Arzu Kader Harmancı Seren (Tehran University of Medical Sciences, 2017)
Background & Aim: When choosing a profession, there are many factors that influence a person's decision, including the profession's image, personal future plans, and the prospect of life-long success. In reference to the nursing profession, this decision is extremely important. This study aims, therefore, to determine the reasons why vocational high school students choose the nursing profession by examining their image perceptions and the future plans related to this choice. Methods & Materials: This study was carried out with 352 nursing students who were selected from four medical vocational high schools in Istanbul. A demographic questionnaire and the "Nursing Image Scale" (NIS) were used for gathering data. For data analysis, percentages were calculated, and independent sample t-test and chi-square test were performed. Results: The average age of the students was 16.7±0.785, with most of the students being female (87.2%) and in their fourth year of attendance (42.6%). A majority of the students had chosen nursing for the ease of securing a job (46.9%), and a majority had a dream profession other than that of nursing but still related to the field of health (65.8%). NIS score averages of the second-year students were lower than those of both the third- and the fourth- year students (p<0.05). Participants who did not have a nurse in the family had higher NIS score averages. Conclusion: Overall, it was determined that the majority of the participating students chose nursing for the purpose of easily securing a job, that the students held a negative perception of the profession and that the students had a dream profession other than that of nursing.